THE EFFECT OF EARLY RETIREMENT COAL-FIRED POWER PLANTS ON CO2 EMISSIONS, LABOR, AND ENERGY GENERATION COSTS IN INDONESIA - Faradila Tomu, Siti
Indonesia's steam coal production is one of the largest in the world, with the largest proven steam coal reserves in the Asia-Pacific region alongside China and Australia. In 2023, Indonesia's coal production was approximately 775 million tons, with domestic coal demand reaching 213 million tons, or about 27% of national coal production. This indicates that the domestic utilization of coal for energy and non- energy purposes has a very promising future. Coal-fired power plants (PLTU) hold the largest share in the installed capacity of fossil energy power plants, with around 42,343 MW or 59% of the total. The trend of coal utilization for PLTUs continues to increase in line with the growing electricity consumption in Indonesia over time. The challenge in using coal as a primary energy source in the future will be significantly impacted by environmental issues. The International Energy Agency projects that all scenarios to meet the 1.5°C target to achieve net zero emissions by 2060 must include a faster reduction in coal fuel usage. One approach is through the early decommissioning of coal-fired power plants, known as early retirement. The early retirement of PLTUs will affect many aspects, including a just transition for coal sector workers, environmental considerations, and economic considerations. Therefore, it is necessary to design and analyze the impact of the early retirement of PLTUs from the upstream to downstream coal sectors as a primary energy source, particularly in relation to environmental, social, and economic aspects. In this study, a system dynamics (SD) model is developed. The SD model is chosen because it can illustrate the complex structure and behavior within the discussed sectoral scope. In this study, the early retirement model of coal-fired power plants consists of several subsystems developed according to the real system. The early retirement of coal-fired power plants will significantly impact environmental aspects, employment, generation costs, and the reliability of the national electricity supply. From an environmental perspective, early retirement of coal-fired power plants can reduce power plant CO2 emissions by approximately 176,093,000 tons of CO2 and greenhouse gas emissions in the coal mining sector by around 7,396,000 tons of CO2 equivalent during the early retirement period (2027-2030). Job losses in the coal mining sector are estimated to be around 11,992 workers (2027-2030), while in the electricity sector, job losses are estimated at around 1,385 workers (2027-2030). However, job creation due to the development of renewable energy power plants is estimated at around 4,531 workers (2027-2030). In the future, the early retirement of coal-fired power plants will significantly increase electricity generation costs, with the average increase estimated at around IDR 4.81 per kWh or approximately IDR 1,775 billion per year during the early retirement period. The early retirement of coal-fired power plants has the potential to cause national electricity supply shortages, so mitigation measures must be carefully planned, considering all risks and benefits. The implementation of early retirement for coal-fired power plants in the future must consider the three pillars of power plant development: affordability (least cost), security of supply (reliability), and acceptability (environmental consideration) to ensure that all these aspects are adequately addressed.